Excited-state dynamics in perylene-based organic semiconductor thin films: theory meets experiment - Wirsing, Sara; Hänsel, Marc; Tegeder, Petra (The journal of physical chemistry. C, Energy, materials, and catalysis, 2019)
Perylene-based organic semiconductors are widely used in organic electronic devices. Here, we studied the ultrafast excited-state dynamics in diindenoperylene (DIP) and dicyanoperylene-bis(dicarboximide) (PDIR-CN2) thin films, respectively, after optical excitation using femtosecond (fs) time-resolved second harmonic generation in combination with large scale quantum chemical calculations. In DIP, the initial optical excitation leads to the formation of delocalized excitons, which localize on dimers on a ultrafast time scale of <50-150 fs depending on the excitation energy. In contrast, in PDIR-CN2, the optical excitation directly generates localized excitons on monomers or dimers. In both DIP and PDIR-CN2, localized excitons decay within hundreds of fs into Frenkel-like trap sites. The relaxation to the ground state occurs in DIP on a time scale of 600 ± 110 ps. In PDIR-CN2, this relaxation time is 1 order of magnitude faster (62 ± 1.8 ps). The differences in the exciton formation and decay dynamics in DIP and PDIR-CN2 are attributed to differences in the aggregation as well as to the respective structural and energetic disorder within the materials. Our study provides important insights into the exciton formation and decay dynamics in perylene-based organic compounds, which is essential for the understanding of the photophysics of these molecules in thin films.
Gesehen am 29.01.2020